Discovery of new biomarkers for malignant mesothelioma - Creaney, Jenette (Curr Pulmonol Rep, 2015)
Malignant mesothelioma is an asbestos-induced, aggressive tumour with limited treatment options and very poor outcome. Currently, there are no tumour biomarkers in widespread clinical use for this disease. Soluble mesothelin is the most intensively investigated mesothelioma biomarker and has been approved by the US FDA primarily as a tool for monitoring patient response and progression. Mesothelin is elevated in the blood and effusions of patients with mesothelioma, and is rarely elevated in people with benign disease with normal renal function. However, the sensitivity of mesothelin limits its use as a stand-alone tool for the screening of the asymptomatic asbestos-exposed population—one of the primary aims of mesothelioma biomarker studies. Thus, there is an intense research effort focused on the identification of new and/or novel biomarkers for mesothelioma. Some of the challenges associated with biomarker discovery in mesothelioma are discussed.